VERDICT MRI validation in fresh and fixed prostate specimens using patient‐specific moulds for histological and MR alignment. (19th February 2019) - Bailey, Colleen; Bourne, Roger M.; Siow, Bernard; Johnston, Edward W.; Brizmohun Appayya, Mrishta; Pye, Hayley; Heavey, Susan; Mertzanidou, Thomy; Whitaker, Hayley; Freeman, Alex; Patel, Dominic; Shaw, Greg L.; et al.
Abstract : The VERDICT framework for modelling diffusion MRI data aims to relate parameters from a biophysical model to histological features used for tumour grading in prostate cancer. Validation of the VERDICT model is necessary for clinical use. This study compared VERDICT parameters obtained ex vivo with histology in five specimens from radical prostatectomy. A patient‐specific 3D‐printed mould was used to investigate the effects of fixation on VERDICT parameters and to aid registration to histology. A rich diffusion data set was acquired in each ex vivo prostate before and after fixation. At both time points, data were best described by a two‐compartment model: the model assumes that an anisotropic tensor compartment represents the extracellular space and a restricted sphere compartment models the intracellular space. The effect of fixation on model parameters associated with tissue microstructure was small. The patient‐specific mould minimized tissue deformations and co‐localized slices, so that rigid registration of MRI to histology images allowed region‐based comparison with histology. The VERDICT estimate of the intracellular volume fraction corresponded to histological indicators of cellular fraction, including high values in tumour regions. The average sphere radius from VERDICT, representing the average cell size, was relatively uniform across samples. The primary diffusion direction from the extracellular compartment of the VERDICT model aligned with collagen fibre patterns in the stroma obtained by structure tensor analysis. This confirmed the biophysical relationship between ex vivo VERDICT parameters and tissue microstructure from histology. Abstract : Using a patient‐specific mould with landmarks to guide a rigid registration procedure, VERDICT model parameters from diffusion in ex vivo prostate were compared with histological correlates. The effects of fixation on model parameters related to tissue microstructure was minimal. Regions with higher cell fraction on histology had higher intracellular fraction on VERDICT, and directions of anisotropic diffusion corresponded to orientation patterns in the stroma.